Characterisation of glycoproteins using a quadrupole time‐of‐flight mass spectrometer configured for electron transfer dissociation. (1st October 2013) - Williams, Jonathan P.; Pringle, Steven; Richardson, Keith; Gethings, Lee; Vissers, Johannes P. C.; De Cecco, Martin; Houel, Stephane; Chakraborty, Asish B.; Yu, Ying Qing; Chen, Weibin; Brown, Jeffery M.
<x xml:space="preserve">Abstract</x> RATIONALE Electron transfer dissociation (ETD) within ion trapping mass spectrometers has proven to be a useful tool for the characterisation of post‐translational modifications. In this study, we describe the implementation of ETD upon a modified quadrupole time‐of‐flight (Q‐ToF) system and methods for the analysis of glycoproteins. METHODS Liquid chromatography electrospray ionisation mass spectrometry (LC/ESI‐MS) was performed using a hybrid quadrupole/ion mobility/oa‐ToF mass spectrometer equipped with ETD functionality. 1, 4‐Dicyanobenzene reagent anions necessary for the ETD reaction were generated from a glow discharge region located within the ESI source block. ETD reactions occurred in the stacked ring travelling wave ion guide (located after the quadrupole mass filter and prior to the oa‐ToF mass analyser). LC/ETD was performed upon 'super‐charged' tryptic glycopeptide ions produced from the recombinant monoclonal antibody trastuzumab. LC/ETD was also performed on ions from the smaller glycopeptides obtained from erythropoietin. RESULTS ETD performed upon the quadruply 'super‐charged' N‐linked glycopeptide ions of trastuzumab and the triply charged O‐linked glycopeptide ions of erythropoietin provided both glycosylation site assignments and full sequence information, respectively. Tandem mass (MS/MS) spectra employing collision‐induced dissociation (CID) were dominated by oxonium product ions hampering full peptide sequence characterisation. CONCLUSIONS LC/ETD on the Q‐ToF system proved effective at characterising a number of different N‐linked glyco‐forms of the tryptic peptide, EEQYNSTYR, from trastuzumab as well as glyco‐forms from the O‐linked tryptic peptide, EASIPPDAASAAPLR, from erythropoietin. The data demonstrates that the glycopeptide site heterogeneity of trastuzumab and erythropoietin can be accurately characterised. In addition, the post‐column mixing of the super‐charging reagent, m‐NBA, is an effective method to increase the precursor ion charge state and to improve ETD reaction efficiency. Copyright © 2013 John Wiley & Sons, Ltd.